Displacement and Disease: HIV Risks and Healthcare Gaps Among Refugee Populations - AKM Ahsan Ullah (Venereology)
Forced displacement exacerbates health vulnerabilities, particularly regarding HIV prevention, diagnosis, and treatment. Refugees often experience heightened exposure to HIV due to precarious living conditions, sexual violence, and healthcare access barriers. Background: Structural inequalities, legal precarity, and stigma hinder HIV care for refugees, especially in resource-limited settings. Excluded from national health programs, refugees often depend on underfunded humanitarian aid. Cultural stigma, limited awareness, and mobility constraints further heighten their vulnerability. Methods: This study draws on a review of peer-reviewed articles, policy documents, and case studies from refugee-hosting countries. It examines healthcare access, service provision gaps, and policy responses to HIV among displaced populations. Results: The article highlights systemic barriers to HIV services, including inadequate testing, inconsistent treatment availability, and cultural barriers to care. Policy frameworks often fail to integrate refugees into national HIV programs, exacerbating health disparities. Conclusions: The exclusion of refugees from national healthcare, compounded by stigma and mobility constraints, deepens health disparities and heightens HIV transmission risks. Without targeted interventions and inclusive health systems, refugees face disproportionate HIV-related morbidity, endangering broader public health in host communities.